The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jog.15176
|View full text |Cite
|
Sign up to set email alerts
|

Alarin: A new predictive marker in infertile women with polycystic ovary syndrome: A case–control study

Abstract: Aim: There is scant evidence concerning the relationship of alarin concentrations for polycystic ovary syndrome (PCOS) status in the existing literature. Therefore, we aimed to reveal the relationship about predictive value of serum alarin concentrations for PCOS risk in infertile women. Methods: This prospective case-control study included a total of 151 infertile women who met eligibility criteria of the study. Infertile women diagnosed with PCOS formed the study group (n = 80). Women with diagnoses of unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 28 publications
(56 reference statements)
1
7
0
2
Order By: Relevance
“…It has also been reported that patients with MetS have significantly higher blood alarin levels than healthy subjects (45). This is further supported by another human study, which indicates that blood alarin levels are higher in women with MetS than controls (61). Alarin was shown to have a positive correlation with fasting blood glucose (FBG), body mass index (BMI), waist circumference, blood pressure, triglyceride, total cholesterol, glycosylated hemoglobin (HbA1c), homeostasis model assessment of b-cell function (HOMA-b), and HOMA of IR (HOMA-IR) in patients with MetS (45).…”
Section: Obesity and Metabolic Syndromesupporting
confidence: 72%
See 3 more Smart Citations
“…It has also been reported that patients with MetS have significantly higher blood alarin levels than healthy subjects (45). This is further supported by another human study, which indicates that blood alarin levels are higher in women with MetS than controls (61). Alarin was shown to have a positive correlation with fasting blood glucose (FBG), body mass index (BMI), waist circumference, blood pressure, triglyceride, total cholesterol, glycosylated hemoglobin (HbA1c), homeostasis model assessment of b-cell function (HOMA-b), and HOMA of IR (HOMA-IR) in patients with MetS (45).…”
Section: Obesity and Metabolic Syndromesupporting
confidence: 72%
“…Alarin was shown to have a positive correlation with fasting blood glucose (FBG), body mass index (BMI), waist circumference, blood pressure, triglyceride, total cholesterol, glycosylated hemoglobin (HbA1c), homeostasis model assessment of β-cell function (HOMA-β), and HOMA of IR (HOMA-IR) in patients with MetS ( 45 ). Other studies have also found positive correlations between serum levels of alarin and BMI, waist circumference, blood pressure, triglyceride, FBG, HbA1c, fasting insulin, and HOMA-IR ( 58 , 61 ). Furthermore, alarin was identified as an independent predictor of the risk factors of MetS, including central obesity, IR, dyslipidemia, hyperglycemia, and hypertension ( 45 ).…”
Section: Role Of Alarin In Various Disease Conditionsmentioning
confidence: 91%
See 2 more Smart Citations
“…Elevated circulating alarin level, associating with increased LH concentration, was found in infertile women with poor ovarian reserve patterns [ 36 ]. Further research by this team confirmed a higher serum alarin concentration in the infertile women diagnosed with polycystic ovary syndrome (PCOS) and a positive correlation between serum alarin and LH level only in the PCOS women rather than other unexplained infertile [ 37 ]. To our knowledge, this is the first study to evaluate the relationship between serum alarin levels and the risk of CVD.…”
Section: Discussionmentioning
confidence: 99%